International perspective on guidelines and policies for child custody and child maltreatment risk evaluations: A preliminary comparative analysis across selected countries in Europe and North America - Zumbach, Jelena; Brubacher, Sonja P.; Davis, Frank; de Ruiter, Corine; Ireland, Jane L.; McNamara, Kathleen; October, Martta; Saini, Michael; Volbert, Renate; Laajasalo, Taina (Frontiers in Psychology, 2022)
The purpose of this paper is to provide an systematic international preliminary comparison on how child custody and child maltreatment risk assessments are conducted in selected various Western countries, and how the assessments are informed by best practice guidelines. Another aim is to increase knowledge on how the guidelines and best-practice standards could be developed further to reflect recent research findings. A total number of 18 guidelines were included in the analyses: 4 from Canada, 5 from the US, 3 from the UK, 3 from the Netherlands, 2 from Finland, and 1 from Germany. We conducted a systematic content analysis of the included guidelines in the database, focusing on how the guidelines address the best interest of the child criteria, guidelines for conducting the assessments, considerations for evaluative criteria, and specific guidance for conducting specific assessment procedures (e.g.e.g., interviews, observations). Findings show that the qualifications of and training provided to evaluators in child custody and child maltreatment risk evaluations are largely heterogeneous across the countries represented. Guidelines differ in whether and how they highlight the importance of evidence-based practices and scientifically validated assessment measures. Implications are drawn from the review and contextualized by international expert authors in the fields of forensic psychology, and family law. The authors provide both commentaries and suggestions to improve the development of standard methods for conducting both child custody and child maltreatment risk evaluations and to consider a more transparent and judicious use of social science research to guide methods and the recommendations offered within these assessments.